Challanging Globalization Era by Reconstruction And Reposition of Islamic Education System - Indah Kusuma Dewi (Sustainable, 2021)
There are many issues related to the progress of islamic education especially in Indonesia. This paper tried to explore the strategies in improving the quality of islamic education by reconstruction of elamic education institute. The qualitative approach was used in collecting the data from various resources. The findings showed that in order to optimize quality of education and facing the globalization challanges, Islamic leaders need to emigrate, mainly in terms of the reconstruction of a more professional managerial aspects and the improvement of quality of education, providing quality assurance, excellent service, and responsibility for its work for students, parents, and community as the stakeholdersmoreover, the implementation of Islamic education in school, the required move is related to the reconstruction of the methodological aspect, from a doctrinaire and dogmatic-traditional learning leads to a more dynamic and contextual-actual one. To implement the contextual approach requires some basic principals, among others: philosophical approaches to understandreligious texts in order not to lose actual, contextual, and fresh ideas, as well as the need to understand and willingness to accept different religious mindset.